Repositioning documentary film in Malaysia: an empirical study of production criteria and practices / Khairulfazi Haji Sa'ari - Sa'ari, Khairulfazi (2015)
During the Malaysia Film Unit (MFU) era, Malaysia was renowned for producing good documentary and was a significant documentary film producer in Asia. The digital revolution has led to a new interest in documentary which has brought about the need for Malaysia to reform and reposition its documentary film production environment. However, despite the various government efforts it is still underdeveloped and its quality is generally considered to be low. This study examined the state of documentary in an effort to ameliorate the current practices of documentary production in Malaysia and, to identify essential criteria that are vital to producing documentary, determine the challenges to the current film makers and to make recommendations as to ways to improve the existing practices. A mixed methodology was utilized. A total of 124 self-administered survey questionnaires were received out of the 198 sent out to active practitioners in the Klang Valley. Outcomes from the survey became the basis for conducting the in-depth interviews during which fifteen major documentary players, which include regulatory bodies, policy makers and all those involved in the industry, were interviewed, in order to gain better insights into documentary production in Malaysia. The results of the study suggests that there is a lack of knowledge and understanding of documentary production among local filmmakers; both in the production aspect (technical know-how) as well as in the creation of content. The findings also reveal that in order to produce successful documentary, both its form and content must be of a high standard, thus emphasizing that the theoretical knowledge and operational skills are equally crucial. The study proposes a framework of 'Essential Production Criteria' (EPC), which is a set of guidelines for producing successful documentary. Additionally, the study offers a documentary repositioning model to help improve and to elevate the current state of documentary and hence contribute towards repositioning documentary in Malaysia.